2015
DOI: 10.1002/ajp.22450
|View full text |Cite
|
Sign up to set email alerts
|

Development of a partner preference test that differentiates between established pair bonds and other relationships in socially monogamous titi monkeys (Callicebus cupreus)

Abstract: Partner preference, or the selective social preference for a pair mate, is a key behavioral indicator of social monogamy. Standardized partner preference testing has been used extensively in rodents but a single test has not been standardized for primates. The goal of this study was to develop a partner preference test with socially monogamous titi monkeys (Callicebus cupreus) adapted from the widely used rodent test. In Experiment 1, we evaluated the test with pairs of titi monkeys (N=12) in a three-chambered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 43 publications
4
37
0
Order By: Relevance
“…They show a behavioral preference for their partner over a stranger (Carp et al, 2016); their partner can buffer their stress response to novelty (Hennessy et al, 1995; Mendoza et al, 2000); and they display distress upon separation from their partner, which is not reduced by the presence of another animal (Mendoza and Mason, 1986a,b; Mendoza, 1991; Laugero et al, 2011; Ragen et al, 2012). Distress is displayed both physiologically by increased cortisol concentrations and behaviorally by contact calls for the mate and increased locomotion (Mendoza et al, 2000; Ragen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…They show a behavioral preference for their partner over a stranger (Carp et al, 2016); their partner can buffer their stress response to novelty (Hennessy et al, 1995; Mendoza et al, 2000); and they display distress upon separation from their partner, which is not reduced by the presence of another animal (Mendoza and Mason, 1986a,b; Mendoza, 1991; Laugero et al, 2011; Ragen et al, 2012). Distress is displayed both physiologically by increased cortisol concentrations and behaviorally by contact calls for the mate and increased locomotion (Mendoza et al, 2000; Ragen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Much of our understanding of pair-bonding in primates comes from the study of the socially monogamous titi monkey ( Callicebus cupreus ), which forms selective and enduring pair-bonds between a single adult male and female (Mason, 1966). This relationship, and attachment relationships more broadly, involve specific preference for and proximity maintenance to the attachment figure (Carp et al, 2015), physiological and affective response to involuntary separation from the attachment figure (Hennessy, 1997), and social buffering of stress responses in the presence of the attachment figure that does not occur in the presence of another individual (Mason and Mendoza, 1998). …”
Section: Introductionmentioning
confidence: 99%
“…Animals were fed twice daily (0830 and 1330 h) a diet consisting of New World monkey chow, rice cereal, banana, apples, raisins, and baby carrots and water was available ad libitum . Further details of husbandry and training are available elsewhere (Tardif et al, 2006), with caging identical to that described in (Carp et al, 2016). …”
Section: Methodsmentioning
confidence: 99%
“…They duet, maintain small territories which they defend against intrusion, and the male is the main carrier of the infants (Mason, 1966, 1968, Mendoza and Mason, 1986b). Adult pairs display many characteristics of a pair bond, including preference for their partner (Carp et al, 2016), distress upon separation (Mendoza and Mason, 1986a), and the ability of the partner to buffer stress (Mendoza et al, 2000). In a previous study, we showed that males that had been in long-term pairs, vs. males that were not paired, showed many differences in regional cerebral glucose metabolism (rCGM) using positron emission tomography (PET) with [ 18 F]-fluorodeoxyglucose (FDG)(Bales et al, 2007).…”
Section: Introductionmentioning
confidence: 99%